2003
DOI: 10.1148/radiol.2281020709
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence Effect in a Laboratory Environment

Abstract: The consistency in the results and the size of this study suggest that with laboratory conditions, if a prevalence effect exists, it is quite small in magnitude; hence, it will not likely alter conclusions derived from such studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(80 citation statements)
references
References 21 publications
2
78
0
Order By: Relevance
“…; one was suitable [25]. The secondary search (Table 2) identified 2828 publications with the full text retrieved for 34: ultimately 6 were included [6,13,[26][27][28][29] and 28 rejected because the research focused on case-specific information. The tertiary search (Table 3) identified 74 MeSH terms which were combined into 18 Boolean search strings: These identified 111 potential articles with a further 2 via snowballing; 5 articles were ultimately included [11,12,[30][31][32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…; one was suitable [25]. The secondary search (Table 2) identified 2828 publications with the full text retrieved for 34: ultimately 6 were included [6,13,[26][27][28][29] and 28 rejected because the research focused on case-specific information. The tertiary search (Table 3) identified 74 MeSH terms which were combined into 18 Boolean search strings: These identified 111 potential articles with a further 2 via snowballing; 5 articles were ultimately included [11,12,[30][31][32].…”
Section: Resultsmentioning
confidence: 99%
“…While these potential "laboratory effects" [10,11] have been discussed in the methodology literature [6,[11][12][13][14], their impact remains unverified. To attempt to quantify their magnitude, we performed a systematic review of studies where the context of interpretation was manipulated or investigated (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Gur et al 5 found that varying prevalence levels between 2% and 21% did not affect the diagnostic accuracy of chest radiograph assessment. Likewise, we did not find a prevalence effect for our three primary outcomes, which were chosen to represent visual search and decisionmaking.…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, a systematic review 3 found only three medical imaging studies [4][5][6] that assessed the impact of experimentally modified prevalence on reader diagnosis. Subsequent studies have been published, [7][8][9][10] but the relationship between prevalence and interpretation accuracy remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation